The Workplace of the Spirituality and Its Impact on the Psychological Empowerment of Employees (An Analytical Study of the Opinions of a Sample of the Teaching Staff at Al-Umid University in Karbala Governorate) - أحمد حامد عباس; يزن سالم محمد (Iraqi Journal for Administrative Sciences, 2024)
The current study aims to test the relationship between the study variables of workplace spirituality, represented by its dimensions (meaningful work, sense of community, and fit between individual and organizational values), and psychological empowerment of employees, represented by its dimensions (competence, impact, meaning, and autonomy) in the research organization. A hypothetical model was developed that illustrates the nature of the relationships between the independent and dependent variables of the study and their sub-dimensions. In order to achieve the objectives of the study, a questionnaire. The questionnaire was designed with 31 items that covered all dimensions of the study. With regard to the field of study, Al-Umaid University in Karbala Governorate was chosen as the field of study. The opinions of a sample of 130 members of the teaching staff. The data from the field side of the study were analyzed using a number of statistical methods, including the statistical package SPSS (26) and AMOS V25. It was concluded that there is a moral relationship between the spirituality of the workplace and the psychological empowerment of employees.